ANALYSIS OF OPERATIONAL ACTIVITIES AND FEASIBILITY OF PURSE SEINE FISHING GEAR AT THE COASTAL FISHING PORT (PPP) SADENG, GUNUNGKIDUL REGENCY, YOGYAKARTA - MANIK, AGUSTINA SARTIKA YOS EKARISTI; SARI, RATNA JUITA (JURNAL PERIKANAN DAN KELAUTAN, 2025)
Purse seine fishing gear has advantages in the efficiency of catching large quantities of pelagic fish and is considered environmentally friendly because it does not damage the seabed. Handling fish catches from purse seine fishing gear at the Sadeng Coastal Fisheries Port (PPP), there are two types, namely by using salt and ice which can maintain freshness and increase the selling price. This shows that the feasibility of purse seine using ice and salt can improve community welfare and is feasible to be developed. The purpose of this study is to analyze operational activities (construction, fishing gear operating techniques, area and season of operation, size of vessels and engines) and the feasibility of purse seine fishing gear at the Sadeng Beach Fishing Port. The research was carried out by descriptive method, sampling by purposive sampling. The analysis was carried out by explaining the operation activities of the purse seine ship from preparation, determination of fishing areas, travel, the process of capture, transportation and management of catches on board, and landing. The 35 GT purse seine catching unit has a lower fixed cost because the depreciation costs and licensing fees that must be incurred are lower than the 45 GT purse seine fishing unit. Based on calculations, an average R/C value of 1.3121 was obtained. This indicates that the R/C value > 1, which means that the venture is profitable and worth developing.Keywords: Feasibility, Fishing Gear, Purse Seine, Sadeng Beach Fishing Port